Effect of Impurity Concentration on Magnetic Properties of SnO2 Nanoparticle - Saravanakumar1, M.; Agilan2, S.; Muthukumarasamy2, N.; Rukkumani3, V.; Marusmy2, A.; Ranjitha2, A. (Asian Journal of Chemistry, 2014)
Undoped and Mn doped SnO2 nanoparticles prepared by co-precipitation method reveal polycrystalline nature with prominent peaks along (110), (101), (211) and (310) planes. All the samples are nanocrystalline with particle size lying in the range of 4.8-5.6 nm calculated by DS formula. As prepared SnO2 nanoparticles exhibit single tetragonal crystalline phase. The HRTEM results were confirmed by the Scherrer equation using FWHM values of the main peaks in the XRD diffraction pattern. Undoped and Mn doped SnO2 synthesized successfully confirms by EDAX Spectra. UV-visible absorption and photoluminescence spectroscopy shows the recombination of electrons in singly occupied oxygen vacancies with photoexcited holes in the valence band. UV-visible absorption spectral studies showed a peak at 300 nm. Broad UV emission at 426 nm is observed in photoluminescence spectra of the films along with a blue emission when excited at 385 nm wavelength. Magnetic measurements revealed that all samples exhibit room temperature ferromagnetism, which is identified as an intrinsic characteristics. Pure SnO2 nanoparticles showed diamagnetism , SnO2 with lower Mn content show the larger magnetization and with increasing Mn content the ferro magnetization and varies retenivity and coercivity in the range of 0.002-0.014 and 122-183.